Modelling the impedance response of graded LiFePO4 cathodes for Li-ion batteries - Drummond, R; Cheng, C; Grant, PS; Duncan, SR (IOP Publishing, 2022)
Graded electrodes for Li-ion batteries aim to exploit controlled variations in local electrode microstructure to improve overall battery performance, including reduced degradation rates and increased capacity at high discharge rates. However, the mechanisms by which grading might deliver performance benefit, and under what conditions, are not yet fully understood. A Li-ion battery electrochemical model (a modified Doyle-Fuller-Newman type model capable of generating impedance functions) is developed in which local microstructural changes are captured in order to understand why and when graded electrodes can offer performance benefits. Model predictions are evaluated against experimental electrochemical impedance data obtained from electrodes with micro-scale, controlled variations in microstructure. A region locally enriched with carbon at the electrode/current collector interface is shown to significantly reduce the overpotential distribution across the thickness of a LiFePO4-based Li-ion battery cathode, resulting in a lower charge transfer resistance and impedance. The insights gained from the LiFePO4-based electrodes are generalised to wider design principles for both uniform and graded Li-ion battery electrodes.